KAJIAN PEMANFAATAN E-LEARNING BeSMART-UNY SEBAGAI MEDIA PEMBELAJARAN - Wahidin Abbas (Kaunia: Integration and Interconnection Islam and Science, 2014)
This research is aimed to measure the further of e-learning usage as instructional media BeSmart UNY for Lecturers and Students in the Faculty of Engineering UNY. E-learning usage is measured by parameters, which are computer knowledge, e-learning knowledge, e-learning frequency access, and e-learning effects for learning process. Research was conducted by survey method and direct observation on the website BeSmart UNY for all study programs in the Faculty of Engineering UNY to measure how far the e-learning usage. The data was collected through field surveys, interviews directly to lecturers and students, as well as the distributing of the questionnaire. The data was analyzed then by a descriptive method. The result showed that the e-learning usage by lecturers and students was quite good with an average score of 3.04/4on a Likert scale. E-learning usage also provides a significant increase in learning motivation with an average score of 3.37/4, but not on the learning outcomes and time completion yet.